Prediction of aerodynamic performances of a gun launched micro air vehicle. (1st January 2014) - Gnemmi, Patrick; Rey, Christian; Meder, Kevin
The study deals with the prediction of the aerodynamic performances of the gun launched micro air vehicle (GLMAV) platform by using the ANSYS CFX code. The validation of the numerical simulation on a micro two-bladed rotor was carried out in 2012 by the comparison of the computed thrust and torque with the measured ones and by using the experience gained from all previous computational investigations. After that, also in 2012, the computation of aerodynamic performances of a first version of the two coaxial counter-rotating rotors of the GLMAV was carried out for the hovering flight. Now, the goal of this paper consists in determining the rotation speeds of the rotors which allows a second version of the GLMAV platform to be slowed down from the rotor deployment phase up to the hovering flight. The power of each brushless motor which should be embedded in the platform is also determined from the results of the computation.